THE EFFECT OF JOB SECTORS ON ANXIETY: AN EXPLORATORY STUDY AMONG LOW INCOME MUSLIM FAMILY DURING MCO COVID-19 - Nur Yani Che Hussin; Raja Nurul Hafizah Raja Ismail (Journal of Islamic, Social, Economics and Development, 2021)
Coronavirus or known as COVID-19 has impacted worldwide and has been declared as a pandemic in 2020. Because of this, there are many mental health cases that arise due to COVID-19 pandemic such as increases in depression symptoms, anxiety and stress that affected to all people regardless of their age. Anxiety also happens because of the fear arises as the number of COVID-19 cases increasing, the loss of job, also changes in educational system and so on. Anxiety is a state of mind marked by tense emotions, nervous thoughts, and physical changes such as elevated blood pressure. Due to this, this study is to examine the level of anxiety level among B40 or low-income Muslim family during Movement Control Order (MCO) during COVID-19 pandemic. The study consists of 128 Muslim respondents from Pahang State which focuses on B40 households and the data collected based on DASS-21 questionnaire online form. As a result, 16 % had severe, and 68 % had extremely severe anxiety. From the data, it shows that among B40 84% of respondents faced severe and extremely severe anxiety during the pandemic. From the result, it is advisable to increase the sample size for more significant value